Feather content of porphyrins in Eurasian eagle owl (Bubo bubo) fledglings depends on body condition and breeding site quality - Galván, Ismael; Delgado, María del Mar; Camarero, Pablo R.; Mateo, Rafael; Lourenço, Rui; Penteriani, Vincenzo (Integrative Zoology, 2018)
Porphyrins are pigments produced in most animal cells during the synthesis of heme, but their importance for external coloration is unclear. Owls (Order Strigiformes) are among the few animals that accumulate porphyrins in the integument, where it could serve as a means of signaling. Here we hypothesized that the porphyrin content of feathers may depend on body condition and breeding site quality in Eurasian eagle owl (Bubo bubo) fledglings and, thus, constitute amplifiers of the quality of the area where they are born. Using high-performance liquid chromatography, we found 2 porphyrins (protoporphyrin IX and coproporphyrin III) in the body feathers of 19 eagle owl fledglings from 7 breeding territories. Coproporphyrin III, but not protoporphyrin IX feather concentration, was positively associated with the body mass of fledglings and with the quality of the breeding sites where they were reared with respect to food quality and availability. As coproporphyrin III is produced under oxidative stress, we suggest that good breeding sites may lead to fledglings in good condition. This, in turn, may make fledglings induce a certain level of free radical and coproporphyrin III production to signal to conspecifics their site-mediated capacity to cope with oxidative stress. This is the first time that porphyrin content in the integument has been found to be related to individual quality, opening a new scenario for studying evolution of animal coloration. I.G. was supported by a Ramón y Cajal Fellowship (RYC2012-10237) from the Spanish Ministry of Economy, Industry and Competitiveness (MINECO). R.L. was supported by a post-doctoral grant (BPD/78241/2011) from the Fundação para a Ciência e a Tecnologia (Portugal POPH/QREN). Peer Reviewed